Urinary catheter related bladder discomforts in early post-operative period after urological surgery, a prospective hospital-based study - Regmi, Prabodh; Kumar Singh, Chandresh; N Shah, Jay (Journal of Chitwan Medical College, 2026)
Introduction: Bladder catheterization is commonly used during major surgeries for urine output monitoring, fluid management, and hemodynamic assessment. Despite its utility, catheter-related bladder discomfort (CRBD) remains under-reported in Nepal. This study aimed to determine the prevalence and severity of CRBD after urological surgery. Method: This prospective study included all adult patients undergoing urological surgery requiring urinary catheterization from 01 Apr to 30 Sept 2025 at Devdaha Medical College, Nepal. Ethical approval was obtained. Exclusion criteria were suprapubic catheter, neurogenic bladder, trauma, pregnancy, emergency surgery, and inability to communicate. Patient-reported symptom severity was categorized into four grades using the Catheter-Related Bladder Discomfort Severity Scale. Associations with clinicodemographic variables were analysed using the Chi-square (or Fisher's exact) test, with a p-value ≤0.05 considered statistically significant. Result: Of the 156 patients enrolled, CRBD was observed in 113(72.4%): mild in 101(64.7%), moderate in 9(5.8%), and severe in 3(1.9%). Patients older than 60 years had a higher prevalence (49/55, 87.3%) compared to those aged 60 years or younger (65/101, 64.4%). The CRBD occurred in 73/96(76.0%) of males and 40/60(66.7%) of females. Based on anaesthesia type, the incidence was 69(75.8%) with general anaesthesia, 44(71.0%) with spinal anaesthesia, and 0/3(0%) with combined general and epidural analgesia. Conclusion: This study demonstrated a high prevalence (72.4%) of catheter-related bladder discomfort after urological surgery. Older age (≥60 years) and general anaesthesia were significantly associated with discomfort, whereas gender, surgery type, duration, and catheter size were not.